KONTRIBUSI BUDAYA KERJA DAN IKLIM KERJA TERHADAP LOYALITAS PENCATAT METER DI PERUSAHAAN X - DWI AFFANDI, RIZAL (Jurnal Ilmu Manajemen (JIM), 2016)
Loyality recorder meter at the X and simultaneous contribtion Job culture and Job climate on employee Loyality recorder meter at the X. This research uses a quantitative approach, the variables were Job culture (X1), Job climate (X2) and Loyality recorder meter (Y). With the number of population in this research as many as 64 employees of the recorder meter at the X. The sample size set out of 64 employees in recorder meter at the X. The instrument of this reseacrh using multiple linear regression analysis with PSAW Statistics 20 software. The results showed that the Job culture has a positive influence on employee performance . Job climate has a positive influence on employee Loyality recorder meter at X. Job culture and Job climate simultaneously have a positive influence employee Loyality recorder meter at the X. Keywords: JobClimate, Job Culture Work, Loyality recorder meter